Everyone goes fishing: Understanding procurement for men, women and children in an arctic community - Shannon, Kerrie (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractThis paper provides insight into Inuit procurement and gender roles. Through a focus on fishing derbies in the Canadian Arctic, this significant aspect of Inuit life is recognized. Many ethnographies and land use studies have previously concentrated on hunting. The fishing derby provides an alternative ethnographic example of procurement. It is an activity in which women, men, children, and elders participate. Women’s roles in the Arctic have often been discussed in terms of gender division of labour or in terms of their complementarity to men’s roles. The fishing derby demonstrates occasions when procurement activities are not necessarily divided along gender lines and thereby reveals a broader understanding of gender roles. The fishing derby is also an ethnographic example of skill as traditional knowledge and may inform how Inuit, and hunter-gatherers more generally, relate to the world around them.